Misdiagnosed avulsion fracture of the Thumb's IP joint in a recreational newcomb ball player - Eden Amiel; Shir Cohen; Elad Epshtein (Journal of Orthopaedic Reports)
A 41-year-old female recreational newcomb ball player presented with a thumb injury initially diagnosed as an avulsion fracture at the interphalangeal joint. Subsequent clinical assessment, including bilateral imaging, revealed the presence of an anatomical sesamoid bone variant in both thumbs, leading to a revised diagnosis of a partial ulnar collateral ligament tear. This case highlights the diagnostic challenges posed by sports injuries with anatomical variants and underscores the value of bilateral imaging in distinguishing between true fractures and common anatomical variations. A comprehensive imaging and physical examination approach can prevent unnecessary immobilization and improve patient outcomes.